Minor change in initial PEEP setting decreases rates of ventilator-associated events in mechanically ventilated trauma patients. Issue 1 (10th May 2020) - Ferrel, Ethan; Chapple, Kristina M; Calugaru, Liviu Gabriel; Maxwell, Jennifer; Johnson, Jessica A; Mezher, Andrew W; Bogert, James N; Soe-Lin, Hahn; Weinberg, Jordan A
Abstract : Background: Surveillance of ventilator-associated events (VAEs) as defined by the National Healthcare Safety Network (NHSN) is performed at many US trauma centers and considered a measure of healthcare quality. The surveillance algorithm relies in part on increases in positive end-expiratory pressure (PEEP) to identify VAEs. The purpose of this cohort study was to evaluate the effect of initiating mechanically ventilated trauma patients at marginally higher PEEP on incidence of VAEs. Methods: Analysis of level-1 trauma center patients mechanically ventilated 2+ days from 2017 to 2018 was performed after an institutional ventilation protocol increased initial PEEP setting from 5 (2017) to 6 (2018)cm H2 O. Incidence of VAEs per 1000 vent days was compared between PEEP groups. Logistic regression modelling was performed to evaluate the impact of the PEEP setting change adjusted to account for age, ventilator days, injury mechanism and injury severity. Results: 519 patients met study criteria (274 PEEP 5 and 245 PEEP 6). Rates of VAEs were significantly reduced among patients with initial PEEP 5 versus 6 (14.61 per 1000 vent days vs. 7.13 per 1000 vent days; p=0.039). Logistic regression demonstrated that initial PEEP 6 was associated with 62% reduction in VAEs. Conclusions: Our data suggest that an incrementally increased baseline PEEP setting was associated with a significantly decreased incidence of VAEs among trauma patients. This minor change in practice may have a major impact on a trauma center's quality metrics. Level of evidence: IV.